1989
DOI: 10.1111/j.1349-7006.1989.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Low Serum Pepsinogen Levels to Detect Stomach Cancer Associated with Extensive Chronic Gastritis in Japanese Subjects

Abstract: Serum pepsinogen levels were measured in 137 stomach cancer patients and compared with those of 288 normal cancer‐free subjects. The serum pepsinogen levels of stomach cancer patients, especially pepsinogen I and the pepsinogen I/pepsinogen II ratio were significantly lower than those of normal controls and correlated well with the extent of chronic gastritis associated with the cancerous stomach. These results were in good accordance with the results of previous studies indicating that the cancer derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 15 publications
3
74
0
1
Order By: Relevance
“…It is simple and inexpensive, and there is no radiation hazard. Early studies from Japan have shown that the serum pepsinogen I level was significantly lower in gastric cancer patients than in normal controls [8,16]. In contrast, no difference was found in serum pepsinogen II levels between the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…It is simple and inexpensive, and there is no radiation hazard. Early studies from Japan have shown that the serum pepsinogen I level was significantly lower in gastric cancer patients than in normal controls [8,16]. In contrast, no difference was found in serum pepsinogen II levels between the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…The single use of pepsinogen tests is by no means sufficient for stomach cancer screening; however, it provides a valuable measure for selecting a population that needs further screening with endoscopy [12][13][14][15]. Serum pepsinogen was introduced for cancer screening to identify individuals with extensive atrophic gastritis [16].…”
Section: Discussionmentioning
confidence: 99%
“…2,39,46,57,69 Authors focused mainly on the diagnosis of atrophy, as its relation with gastric cancer has been reported. If in most Western countries the focus was on the identification of individuals for intervention studies, in Japan, its use was meant to identify those for endoscopic examination, and for the diagnosis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is generally accepted that serum pepsinogen concentrations are related to gastric mucosal lesions, and particularly to chronic atrophic gastritis (CAG). 2,3 At least for intestinal-type gastric carcinoma, CAG is considered to be a preceding condition in the sequential histopathological changes that lead to cancer. 4,5 Pepsinogen has therefore been used as a serological biopsy for more than 20 years in different countries and sets of patients.…”
mentioning
confidence: 99%